Between Domestic and Commonly Known Bankruptcy Prediction Models, How Differ It Can Be? - Muhamad Fiqri Aripin (Universitas Pancasakti Tegal, 2024)
Risk Management become such an important study after 2008 Financial Crisis. As such the needs of research and improvement of Bankruptcy Prediction Models as risk assessment tool is a must. This paper will help the current and upcoming research in related fields in choosing best and suited variables and methodologies that can help revaluation and improvement bankruptcy prediction studies. This a quantitave research by using comparative associative model with non-parametric inferential analysis. To achieve the goal, this study involved four bankruptcy prediction models which two of them are commonly known models (Springate and Zmijewski) and another two are locally made by using data of Indonesia’s. The result from data analysis of 1,860 samples shows that the locally made bankruptcy prediction model or more correctly the Herlina’s Model came as the best performed model because by using suited data for certain economic and financial climate, bankruptcy prediction model can achieve a better result than commonly known models.